The Effectiveness the Power of Two in Speaking Skill in Describing Pictures at the Second Years of Madrasah Nurul As’adiyah Callaccu Sengkang. - As'ad, Muhammad (Prosiding University Research Colloquium, 2019)
Background: This research was about the effectiveness the power oftwo in describing pictures in speaking skill at the second years ofMadrasah Nurul As’adiyah Callaccu Sengkang. The study tried toanswer the problem: “what was effective is the power of two indescribing pictures in enhancing student’s speaking skill?”Purpose: The objectives of the research were to find out theeffectiveness the power of two in describing pictures in enhancingstudents’ speaking skill.Method: This research used pre experimental method. Thepopulation of this research was the second years students ofMadrasah Nurul As’adiyah Callaccu Sengakang Kabupaten Wajo inacademic years 2013/2014. The total number of the population was70 students. The sample of the research was selected by usingpurposive sampling technique. The total numbers of sample were 30students. The instrument of this research was speaking test includingpre-test and post-test. After several meetings, this research found outthat the used of the power of two in describing pictures was effectiveto enhance the students’ speaking skill.Result: The result of this research was the mean score obtained bythe students through the pre-test was 40,18 and post-test was 55,18.The t-test value was higher than t-table (7,31> 2.045). It means thatthere was a significant difference between the result of the students’pre-test and post-test. Therefore, hypothesis H0 was rejected and H1was accepted. It could be said that using the power of two indescribing pictures is effective to enhance the students’ speaking skillat Madrasah Nurul As’adiyah Callaccu Sengkang. Based on the dataabove, the researcher concluded that the power of two in describingpicture was effective to enhance the students’ speaking skill.Therefore, the researcher suggests to English teacher to use thepower of two in describing picture as media in teaching speakingskill.